2022
DOI: 10.3389/fphar.2022.896198
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling for Histologically Fibrotic Stage in Chronic Drug-Induced Liver Injury

Abstract: Background and aims: Chronic drug-induced liver injury (DILI) is a rare but under-researched adverse drug reaction–related disease, which is highly likely to progress into liver fibrosis and even cirrhosis. In this study, metabolomics was used to screen out characteristic metabolites related to the histological progression of fibrosis in chronic DILI and analyze the metabolic changes during the development of fibrosis to explain the underlying mechanism.Methods: Chronic DILI patients who underwent liver biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Nevertheless, this was a serum analysis and therefore might not represent the metabolic environment in fibrotic tissues. Other metabolomics studies performed on patients’ biopsies from idiopathic pulmonary fibrotic lungs 67 and fibrotic liver 68 support the results found for the glucose flux towards the TCA cycle. This is in line with the higher availability of glucose for biosynthesis and mitochondrial oxidation upon TGF-β stimulation.…”
Section: Tgf-β Influences Cellular Metabolism In Myofibroblast Contra...supporting
confidence: 75%
“…Nevertheless, this was a serum analysis and therefore might not represent the metabolic environment in fibrotic tissues. Other metabolomics studies performed on patients’ biopsies from idiopathic pulmonary fibrotic lungs 67 and fibrotic liver 68 support the results found for the glucose flux towards the TCA cycle. This is in line with the higher availability of glucose for biosynthesis and mitochondrial oxidation upon TGF-β stimulation.…”
Section: Tgf-β Influences Cellular Metabolism In Myofibroblast Contra...supporting
confidence: 75%
“…The liver controls the central processes of lipid homeostasis, and disturbed lipid metabolism can contribute to the occurrence and progression of liver fibrosis ( Moustafa et al, 2012 ; He et al, 2022 ). Here, lipidomics was performed, and the results displayed that lipid profiles were varied between the CCl 4 model and normal liver samples, and treatment with Schizandrin C can regulate lipid species in CCl 4 liver.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in adults showed that metabolomics can help establish markers of severity and/or chronicity of DILI. He et al (May 2022) concluded in a study conducted in patients with DILI fibrosis that metabolomic fingerprints suggest that alteration of lipid metabolites is the most important factor in the development of DILI fibrosis [49]. Zhao et al (April 2022), after performing a metabolomic study in patients with DILI, revealed that bile acids and polyunsaturated fatty acids were closely related to the severity and chronicity of DILI, respectively, thus potentially representing potent markers of DILI severity and chronicity [50].…”
Section: Discussionmentioning
confidence: 99%